Outcomes of high volume cataract surgeries at a Lions Sight First Eye Hospital in Kenya - Trivedy, Jyotee (Nepalese Journal of Ophthalmology, 2011)
Background: High volume cataract surgery is practised in many eye centres. Objective: To investigate whether routine high volume cataract surgery can be performed without compromising the quality of surgery. Materials and methods: A retrospective interventional study was carried out at a high volume eye care centre including 368 subjects with cataract operated within 5 randomly selected theatres. Suture-less manual small incision cataract surgery (SICS) with PCIOL was performed in all except nine cases. Results: Of the total, 81.8 % of the patients achieved post-operative uncorrected visual acuity (UCVA) of 6/18 and better by the 4th week. Only 0.3 % had a posterior capsule tear without vitreous loss, 0.5 % posterior capsule tear with vitreous loss and 0.8 % had hyphema. Post-operative examination done at the camp site after Day 30 did not reveal anterior segment complications in any of the patients. Fifteen patients were found to have posterior capsular opacification and had the UCVA between 6/24 – 6/60. Only 12.9 % of the patients had first post operative day complications, which included transient corneal oedema (3.0 %) with less than 10 Descemet folds, transient corneal edema with > 10 Descemet folds (3.6 %), transient corneal edema (4.3 %), shallow anterior chamber (0.3 %) and others like iritis and peaked pupil. Multiple logistic regression analysis showed no significant association between risk factors like age, sex, laterality, pre-operative visual acuity, surgeon, time of surgery and post-operative UCVA. Conclusion: The study results show that high quality cataract surgery can be attained in a high volume setting. Key words: small-incision cataract surgery; surgical outcome; blindness DOI: 10.3126/nepjoph.v3i1.4276 Nepal J Ophthalmol 2011;3(5):31-38